Determination of Cropping Pattern Based on Water Surface Elevation of Weir Using Mathematical Method (Jurnal Teknologi (Sciences & Engineering), 2012)
Waduk merupakan tempat penyimpanan air sementara selama ada kelebihan air dan segera dikeluarkan apabila diperlukan. Ada tiga hal pokok yang harus diperhatikan guna mencapai penggunaan air secara optimum yaitu kapasitas waduk, curah hujan dan pola tanaman yang digunakan. Curah hujan adalah gejala alam yang dapat diperhitungkan dari data meteorologi yang tersedia. Polaa tanam hanyalah faktor yang dapat ditentukan oleh manusia. Tulisan ini akan membahas tentang memperkirakan pola tanam yang akan digunakan dengan membaca elevasi muka air waduk dari pemodelan matematik yang telah dibuat dalam bentuk grafik. Dengan membandingkan data muka air terkini dapat digunakan untuk menentukan pola tanam berikutnya. Kata kunci: pola tanaman; elevasi muka air A weir is temporary water storage when it is excessive during rainy session; and it is drawn out during dry season to meet water demand in the field. There are three important parameters which are affecting the volume of water in the reservoir, i.e., rainfall, cropping pattern, and the reservoirÂ´s capacity. Those three parameters have to be equally balanced as indicated by water level in the weir never spill out or never below the intake elevation. The rainfall is the natural phenomenon that can be predicted by meteorogical data available, while the weir capacity is varied according to the seasons. The cropping pattern is the only factor which can be interfered by human. This study is aiming to predict the crop pattern by monitoring water elevation. Mathematical modelling is presented graphically. By comparing it to the plotting of recent water level data, could be cosidered to predict for the next crop. Key words: cropping pattern; water surface elevation